2021
DOI: 10.1002/ctm2.545
|View full text |Cite|
|
Sign up to set email alerts
|

A methyltransferase‐like 14/miR‐99a‐5p/tribble 2 positive feedback circuit promotes cancer stem cell persistence and radioresistance via histone deacetylase 2‐mediated epigenetic modulation in esophageal squamous cell carcinoma

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is a highly aggressive and treatment‐resistant tumor. The biological implications and molecular mechanism of cancer stem‐like cells (CSCs) in ESCC, which contribute to therapeutic resistance such as radioresistance, remain elusive. Methods Quantitative real‐time polymerase chain reaction, western blotting, immunohistochemistry, and in situ hybridization assays were used to detect methyltransferase‐like 14 miR‐99a‐5p t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Methyltransferases include METTL3, METTL14, WTAP, KIAA1429, and so on. METTL14 is one of the components of the m6A methyltransferase complex discovered in recent years [ 18 ]. METTL14 can participate in the catalysis of m6A by forming a complex heterodimer structure with METTL3, and METTL14 can also form heterodimers with METTL3 to promote the stability of their respective proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Methyltransferases include METTL3, METTL14, WTAP, KIAA1429, and so on. METTL14 is one of the components of the m6A methyltransferase complex discovered in recent years [ 18 ]. METTL14 can participate in the catalysis of m6A by forming a complex heterodimer structure with METTL3, and METTL14 can also form heterodimers with METTL3 to promote the stability of their respective proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, METTL3 was found to be highly expressed in ESCA and may be potentially associated with glycolysis of tumor cells ( Liu et al, 2020d ). Liu et al found that the METTL14/mir-99a-5p/tribble 2 positive feedback pathway can promote the persistence and radiation resistance of ESCC stem cells ( Liu et al, 2021d ). The study of these related genes further confirmed the possibility of YTHDF1 participating in the progression of ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, m6A modification could facilitate the acquisition of CSCs properties via promoting Wnt/β-catenin signaling, thereby inhibiting chemosensitivity of CRC [ 68 ]. Similarly, CSCs generation and radiosensitivity in esophageal squamous cell carcinoma (ESCC) were also influenced by m6A methyltransferase METTL14 [ 72 ].…”
Section: M6a Modification Involved In Regulating Cancer Therapeutic R...mentioning
confidence: 99%